Evidence for a curvilinear relationship between posttraumatic growth and posttrauma depression and PTSD in assault survivors. - Kleim, B; Ehlers, A (2009)
Two studies of assault survivors (Ns = 180, 70) examined associations between posttraumatic growth (PTG) and posttrauma psychopathology. Both studies found significant curvilinear associations between PTG and posttraumatic stress disorder, whereas only Study 1 found a curvilinear association between PTG and depression symptom severity. Survivors with no or high growth levels reported fewer symptoms than those who reported moderate growth. Study 1 also investigated potential PTG predictors. Non-Caucasian ethnicity, religiousness, peritraumatic fear, shame, and ruminative thinking style, assessed at 2 weeks, predicted growth at 6 months. Posttraumatic growth may thus be most relevant in trauma survivors who attach enduring significance to the trauma for their lives and show initial distress. Moderate levels of PTG do not seem to ameliorate posttrauma psychopathology.